Identifying differential item functioning (DIF) using item response theory (IRT) in mathematics examination paper / Ling Siew Eng ... [et al.]. - Ling, Siew Eng; Lau, Sie Hoe; Goh, Kaw Sze (2004)
Test scores have serious implications on the examinee's future. Some important decisions such as evaluating the education quality, promoting students to a higher grade, recruiting new staff and for promotion purpose are made based on test scores. When important decisions are made based on test scores, it is very important to avoid bias, which may unfairly influence examinees' scores. Bias is the presence of some characteristics of an item that results in differential performance for individuals of the same ability across ethnic, sex, cultural and religious groups.